Fish Weighning Information System Based on Internet of Things: Sistem Informasi Penimbangan Hasil Tangkapan Ikan Berbasis Internet of Things - Muhammad Takdir Muslihi; Andita Dani Achmad (Unit Penelitian dan Pengabdian Kepada Masyarakat, AK-Manufaktur Bantaeng, 2023)
This study aims to design a system that detects the weight of caught fish at fish auctions in coastal fishing ports (TPI) by utilizing internet of things technology. Fish weight data obtained through measurements by sensors placed under the weighing plate is sent to the database server. Then the fish type data is entered through the web application. The web application will display data on the weight and type of fish in each TPI to the user. The accuracy percentage of the designed scales is 97.168%.